Socio-economic Impact of the Development of Para Lelle Tourism Village, Tatoareng District, Sangihe - Kumaseh, Eunike Irene; Sarapil, Costantein Imanuel; Ikhtiagung, Ganjar Ndaru; Patras, Mareike Doherty (Department of Ocean Engineering, Faculty of Engineering, Hasanuddin University, 2025)
This research aims to determine the impact of developing the Para Lelle tourist village on the socio-economic conditions of fishermen as well as formulating policies for the Government based on this impact analysis. Data collection was carried out by collecting data directly through interviews and observation (direct observation) using questionnaires on fishermen in Para Lelle Village (Para Island) Tatoareng District, Sangihe Islands Regency. Qualitative descriptive data analysis for socio-economic conditions and level of community welfare using a Likert scale approach. Quantitative data analysis to determine the influence of the development of the Para Lelle tourist village on the socio-economic conditions of fishermen using statistical regression analysis methods. Currently, marine tourism activities do not have a significant impact on people's income. Policies that can be taken for the development of the Para Lelle Developing Tourism Village are increasing coordination & communication between the Village Government and Regional Government as well as other stakeholders, increasing the development of public facilities in tourist areas, and increasing the capabilities of local communities.